Research Paper: Simulation of Neutron Absorption of an Aluminum-base Composite Containing Boron Carbide Particles - zahra Safaei; Mohsen Asadi Asadabad; Reza Amini Najafabadi; Javad Mokhtari (فیزیک کاربردی ایران, 2021)
The use of metal matrix composites can provide a combination of desirable properties of metals as well as the special physical properties of neutron absorber reinforcing particles such as boron carbide, which alone may be brittle. Therefore, in the present study on neutron attenuation power of composite shielding, several Al-B4C composite samples with weight fractions of 5, 10 and 20% B4C have been used. In order to investigate the neutron absorption properties of the studied samples, the MCNP Monte Carlo code and the neutron source of the dry channel of the MNSR reactor with a flux of 2.13E+5 n.cm-2.s-1 have been used  ,which provided in nominal reactor power of 30 kW. The results show that the neutron flux in the presence of 5, 10 and 20% boron carbide samples is predicted to be 1.32E+05 n.cm-2.s-1,1.12E+05 n.cm-2.s-1 and 1.07E+05 n.cm-2.s-1, respectively. With this increase in the percentage of reinforcement phase, neutron flux is reduced down to 50%.